Concentration des populations musulmanes et structuration de l’associatif musulman à Bruxelles - Corinne Torrekens (Brussels Studies, 2007)
An estimate of about 160 000 persons, or 17% of the population, is generally accepted for the number of persons of Muslim origin in Brussels. Since national statistics do not include information on religious beliefs, the figure can only be an approximation. To give a more accurate factual understanding of the Muslim presence in Brussels, Corinne Torrekens proposes an analysis of the Muslim associative fabric (non-profit associations) in Brussels, with a map showing the various concentrations of the associations in the Brussels-Capital Region, as well as the lines of fragmentation that divide and structure the Muslim population in Brussels.